Cognitive behavior therapy with a migrant Pakistani in Malaysia: a single case study of conversion disorder - Choudhry, Fahad Riaz; Munawar, Khadeeja; Abdul Khaiyom, Jamilah Hanum; Tam, Cai Lian (Persatuan Psikologi Malaysia, 2019)
This clinical case presents a 24 years old, Muslim Pakistani girl with a history of conversion disorder. Her symptoms comprised fits, restlessness, numbness in legs, poor coordination, and balance, burning during urination and retention. A Cognitive Behavioral Model was used for conceptualizing her problem and devising a management plan based on Cognitive Behavioral Therapy and culturally adapted coping statements. She took 13 therapy sessions and was presented with idiosyncratic case conceptualization. Psychoeducation on the illness, maladaptive thoughts identification, coping statements, and verbal challenging were used in a collaborative way for cognitive restructuring of the client. Behavioral techniques of extinction and behavioral activation were also practiced. The focus of terminal sessions was on anger management and it was found that she needed couple of more sessions in order to help her manage her anger. However, the therapy was terminated on part of client after attainment of short-term goals. The client reported to have 75 % improvement in her overall condition and remained compliant throughout the therapy.